A standard sample for low-temperature impact performance detection and a preparation method thereof
Patent Information
- Application Number
- CN202310173312.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Existing metal impact standards are costly and have complex manufacturing processes. Furthermore, existing standard samples are not suitable for low-temperature impact performance testing, which affects the accuracy of test results.
High-impact polystyrene (HIPS) and linear low-density polyethylene (LLDPE) were used as the base resins. Talc powder compound with D50 particle size of 0.5-2μm and 5-8.5μm was added, and talc powder was modified with coupling agent. In addition, compatibilizer, antioxidant, light stabilizer and lubricant were added. Standard samples were prepared by twin-screw extruder.
This improved the uniformity and stability of the low-temperature impact resistance of standard samples, meeting the requirements for low-temperature impact performance testing, reducing preparation costs, and simplifying the process.
Smart Images

Figure BDA0004099929510000051 
Figure BDA0004099929510000061 
Figure BDA0004099929510000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of standard sample technology, and in particular to a standard sample for low-temperature impact performance testing and its preparation method. Background Technology
[0002] Impact testing is a fundamental test for evaluating whether a material possesses sufficient toughness at the test temperature. Based on the test temperature, impact testing is divided into two types: room temperature impact and low temperature impact. Room temperature impact is conducted at room temperature, generally within the range of (23±2)℃. Low temperature impact involves storing the sample in a low-temperature medium for a certain period, allowing the temperature to reach the required level, and then quickly removing it to complete the impact test. With the widespread application of polymer materials, products often need to adapt to different usage environments and varying temperature conditions. For example, if automotive interior parts have poor low-temperature toughness, cracking under frigid conditions will directly endanger the safety of passengers. Therefore, conducting low-temperature impact testing is crucial to ensuring the safe use of materials.
[0003] Besides the inherent properties of the material itself, the operator's testing techniques and the condition of the equipment can also affect the impact test results. To ensure the accuracy of impact test results, laboratories typically use standard samples for verification.
[0004] CN1074543C discloses an impact standard made of low-carbon steel and a manufacturing method thereof. The impact standard is made of metal. Compared with plastic, metal is more expensive and has a more complex manufacturing process. In addition, the impact energy of metal is generally very high. The standard sample made of metal is suitable for verification by high-energy impact testers, but not entirely suitable for verification of plastic impact test results.
[0005] CN114674648A discloses a standard sample for unnotched impact performance testing and its preparation method, and CN114773732A discloses a standard sample for notched impact strength testing and its preparation method. Both standard samples are only applicable to room temperature. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a standard sample for low-temperature impact performance testing and its preparation method.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A standard sample for low-temperature impact performance testing, the standard sample comprising the following components in parts by weight: 50-90 parts of high-impact polystyrene (HIPS), 10-30 parts of linear low-density polyethylene (LLDPE), 1-10 parts of compatibilizer, 1-10 parts of talc, and 0.3-5 parts of additives; wherein the talc is a compound of talc with a D50 particle size of 0.5-2 μm and talc with a D50 particle size of 5-8.5 μm.
[0009] This invention selects HIPS as the matrix resin. HIPS is a two-phase system composed of a rubber phase and a continuous polystyrene phase, exhibiting good dimensional stability and low water absorption after molding, which is beneficial for the daily storage of standard samples. LLDPE helps improve the impact performance of the system and has relatively good compatibility with HIPS. By adjusting the content of HIPS, LLDPE, and compatibilizer, products with different low-temperature impact strengths can be prepared. This invention uses a blend of two talc powders with different particle sizes. The gaps between coarse particles are filled by fine particles, increasing the contact area between the two talc powders and reducing the interface between talc powder and resin. This reduces the shrinkage rate of the standard samples and improves their uniformity and stability.
[0010] Preferably, the melt flow rate of the high-impact polystyrene measured at 200℃ and 5kg is 4-8 g / 10min; the melt flow rate of the linear low-density polyethylene measured at 190℃ and 2.16kg is 1.5-6 g / 10min. All melt flow rates are measured with reference to GB / T 3682.1-2018. The purpose of limiting the melt flow rates of HIPS and LLDPE is to improve their processing performance and avoid defects such as sample blockage of the injection molding machine head, under-injection, and delamination in the injection molded samples, which would affect the uniformity of the standard samples.
[0011] Preferably, in the compound, the mass ratio of talc powder with a particle size of 0.5-2 μm to talc powder with a particle size of 5-8.5 μm is (1-1.5):(1-3); more preferably, in the compound, the mass ratio of talc powder with a particle size of 0.5-2 μm to talc powder with a particle size of 5-8.5 μm is 1:(1-2). Experiments have shown that when the mass ratio of the two components meets the above-mentioned proportions, the stability of the standard sample is better.
[0012] Preferably, the talc powder is talc powder modified with a coupling agent. The modification method is as follows: at 100-110℃, a diluted coupling agent is added to the talc powder and stirred evenly to obtain the talc powder modified with the coupling agent. The diluent used for dilution is at least one of the solvents such as liquid paraffin, isopropanol, and ethanol, and the mass ratio of the diluent to the coupling agent is 1:(0.8-1). The coupling agent is at least one of titanate coupling agents and silane coupling agents; more preferably, the coupling agent is a titanate coupling agent, such as a composite monoalkoxy titanate (TMC931) or isopropyltris(dioctylpyrophosphate) titanate (TMC-201); the mass fraction of the coupling agent is 1%-2.5% of the talc powder. Modification with a coupling agent can improve the dispersibility of the talc powder and improve the uniformity of the standard sample.
[0013] Preferably, the high-impact polystyrene comprises 60-80 parts by weight, the linear low-density polyethylene comprises 15-25 parts by weight, the compatibilizer comprises 3-8 parts by weight, and the talc comprises 2-7 parts by weight. Optimizing the amounts of the above components can further improve the uniformity and stability of the standard sample.
[0014] Preferably, the compatibilizer is a styrene-butadiene-styrene block copolymer, wherein the mass fraction of butadiene in the styrene-butadiene-styrene block copolymer (SBS) is 60%-80%; more preferably, the mass fraction of butadiene in the styrene-butadiene-styrene block copolymer (SBS) is 60%-70%. The above-mentioned preferred content of butadiene in SBS can improve the impact performance of the standard sample, but an excessively high butadiene content will affect the uniformity of the standard sample.
[0015] Preferably, the additives comprise 0.1-1 parts of an antioxidant, 0.1-2 parts of a light stabilizer, and 0.1-2 parts of a lubricant. The antioxidant is at least one of hindered phenolic antioxidants such as antioxidant 1010 and phosphite antioxidants such as antioxidant 168; the lubricant is at least one of an internal lubricant and an external lubricant; the internal lubricant is at least one of liquid paraffin, stearyl alcohol, polyester wax 691, and microcrystalline wax; the external lubricant is at least one of calcium stearate, zinc stearate, magnesium stearate, and n-butyl stearate; and the light stabilizer is at least one of light stabilizer 622, light stabilizer 4050, light stabilizer 770, and light stabilizer 944. Adding antioxidants, light stabilizers, and lubricants can further improve the overall stability of the standard sample.
[0016] Preferably, the antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant in a mass ratio of 1:(1-2), and the lubricant is a mixture of internal lubricant and external lubricant in a mass ratio of 1:(1-2). The internal lubricant is liquid paraffin, and the external lubricant is zinc stearate. Adding antioxidants can prevent oxidative degradation during resin processing and also prevent significant natural aging of standard samples during routine storage. The internal lubricant can reduce the cohesive forces between polymer molecules, improve internal frictional heating during processing, and increase melt flowability. The external lubricant can improve surface friction between the polymer melt and processing equipment, acting as a release agent. Using a mixture of internal and external lubricants, and optimizing their ratio and specific types as described above, can effectively improve the uniformity and stability of the standard samples.
[0017] Furthermore, this invention also discloses a method for preparing the standard sample for low-temperature impact performance testing, the method comprising the following steps:
[0018] (1) Mix the components evenly according to the proportions to obtain the premix;
[0019] (2) The premixed material is added to a twin-screw extruder for melt extrusion, stranding, cooling, pelletizing, and drying to obtain the standard sample used for low-temperature impact performance testing.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] This invention uses high-impact polystyrene as the base resin and adds linear low-density polyethylene and a compatibilizer to improve the uniformity and stability of its low-temperature impact resistance. Furthermore, by adding talc of two different particle sizes, this invention significantly improves the uniformity and stability of the standard samples, thus meeting the performance requirements of standard samples used for low-temperature impact performance testing. Detailed Implementation
[0022] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0023] Unless otherwise specified, the materials used in the embodiments and comparative examples are commercially available.
[0024] High-impact polystyrene: China National Petroleum Corporation, grade HIPS HIE-1, melt flow rate of 5.5 g / 10 min (200℃, 5 kg);
[0025] Polyethylene 1: Linear low-density polyethylene, Jilin Petrochemical, grade LLDPE 7042, melt mass flow rate is 2g / 10min (190℃, 2.16kg);
[0026] Polyethylene 2: Low-density polyethylene, Daqing Petrochemical, grade LDPE 2426H, melt mass flow rate is 2.1g / 10min (190℃, 2.16kg);
[0027] Talc 1: IMI Fabry-Perot, HTP Ultra 5L, D50 particle size 0.5μm;
[0028] Talc powder 2: Liaoning Xinda Talc Group Co., Ltd., SDC-F7, D50 particle size 2μm;
[0029] Talc 3: Im-Mefabi, HTP3, D50 particle size 3.5μm;
[0030] Talc 4: Guangxi Longsheng Huamei, AH-1250N6, D50 particle size 5μm;
[0031] Talc 5: Wuhan Chengtian Fine Chemical Co., Ltd., CT0638, D50 particle size 8.5μm;
[0032] Talc 6: Guangzhou Qijie Chemical, WF90-10, D50 particle size 10μm;
[0033] Compatibilizer 1: SBS, Sinopec Baling, brand YH-792, butadiene mass fraction is 60%;
[0034] Compatibilizer 2: SBS, Sinopec Baling, brand YH-791, with a butadiene mass fraction of 70%;
[0035] Compatibilizer 3: SBS, Sinopec Baling, brand name YH-796, butadiene mass fraction is 80%;
[0036] Antioxidant: A compound of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio, commercially available;
[0037] Light stabilizer: Light stabilizer 770, commercially available;
[0038] Lubricant 1: Liquid paraffin, commercially available;
[0039] Lubricant 2: Zinc stearate, commercially available;
[0040] Lubricant 3: Stearyl alcohol, commercially available;
[0041] Coupling agent 1: Titanate coupling agent, TMC931, commercially available;
[0042] Coupling agent 2: Silane coupling agent, SIVO214, commercially available;
[0043] The antioxidants, light stabilizers, lubricants 1-3, and coupling agents 1-2 used in the examples and comparative examples are all commercially available products; the melt flow rates mentioned above were all measured with reference to GB / T 3682.1-2018.
[0044] Example 1
[0045] An embodiment of the standard sample for low-temperature impact performance testing according to the present invention is shown in Table 1, and the preparation method is as follows:
[0046] (1) Preheat the high-speed mixer to 100°C, add talc powder and stir for 5 minutes. Dilute the coupling agent with liquid paraffin at a mass ratio of 1:1. Then, spray the diluted coupling agent into the powder in the high-speed mixer in 3 batches at 2-minute intervals and mix evenly to obtain talc powder modified by the coupling agent.
[0047] (2) Add high-impact polystyrene, polyethylene, compatibilizer, modified talc, antioxidant, light stabilizer and lubricant to a high-speed mixer according to the proportion and stir evenly to obtain a premix; the stirring speed is 150 r / min and the stirring time is 3 min.
[0048] (3) The premixed material is added to a twin-screw extruder with a screw length-to-diameter ratio of 40:1 for melt extrusion, stranding, cooling, pelletizing, and drying. The pellets are then injection molded into notched impact test strips with dimensions of 80mm×10mm×4mm to obtain the standard sample used for low-temperature impact performance testing. The melt extrusion conditions are as follows: vacuum controlled at -0.06 to -0.08 MPa, main engine speed 450 r / min, feed rate controlled at 450 kg / h, and the temperatures of each zone are as follows: zone 1 80±10℃, zone 2 170±10℃, zone 3 170±10℃, zone 4 170±10℃, zone 5 170±10℃, zone 6 170±10℃, zone 7 170±10℃, zone 8 170±10℃, zone 9 170±10℃, and die head temperature 190℃.
[0049] Examples 2-13
[0050] The standard sample for low-temperature impact performance testing described in this invention has the formula shown in Table 1, and the preparation method is the same as in Example 1.
[0051] Table 1 (parts by weight)
[0052]
[0053]
[0054] Examples 14-16
[0055] The standard sample for low-temperature impact performance testing described in this invention differs from that in Example 1 only in the talc used. In Example 14, talc 2 is used instead of talc 1; in Example 15, talc 5 is used instead of talc 4; and in Example 16, talc 2 is used instead of talc 1, and talc 5 is used instead of talc 4.
[0056] Example 17
[0057] The standard sample for low-temperature impact performance testing described in this invention differs from that in Example 1 only in that talc powder 1 and talc powder 4 are not modified with coupling agent, and the modification treatment in step (1) is not performed in the preparation method.
[0058] Comparative Examples 1-4
[0059] The only difference between Comparative Examples 1 to 4 and Example 1 is the type of talc used. In Comparative Example 1, talc 3 is used instead of talc 1. In Comparative Example 2, talc 6 is used instead of talc 4. In Comparative Example 3, only talc 1 is used, and talc 4 is not added. The weight of talc 1 is 5 parts. In Comparative Example 4, only talc 4 is used, and talc 1 is not added. The weight of talc 4 is 5 parts.
[0060] Comparative Example 5
[0061] The only difference between Comparative Example 5 and Example 1 is that different polyethylene is used, with polyethylene 2 replacing polyethylene 1.
[0062] The standard samples described in the above embodiments and comparative examples were subjected to homogeneity and stability tests in sequence. Before the test, the samples were conditioned at 23°C for 24 hours and then frozen at -40°C for 4 hours. The specific test methods and results are as follows:
[0063] (1) Uniformity Test: Ten groups of samples were randomly selected from the packaged standard samples for uniformity verification. Using a cantilever pendulum impact tester, each group of samples was tested according to standard GB / T 1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams". Two beams were tested in each group. One-way ANOVA (F-test) was used to analyze the test results. If the F-value is less than the specified limit (F... 0.05(9,10) =3.02), indicating that there is no significant difference within and between samples, and the samples are homogeneous. The test results are shown in Table 2.
[0064] (2) Stability Test: After the prepared standard samples were sealed and stored at room temperature in the dark for 6 months, 10 groups of samples were randomly selected from the standard samples. Using a cantilever pendulum impact tester, each group of samples was tested according to standard GB / T 1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams". Two beams were tested in each group. The test results were analyzed using the t-test method. The uniformity test data was taken as one average value. If the t-value was less than the specified limit (t... 0.05(20+20-2) =2.024), proving that the standard sample did not undergo significant changes. The test results are shown in Table 3.
[0065] Table 2
[0066]
[0067]
[0068]
[0069] Table 3
[0070]
[0071]
[0072]
[0073]
[0074]
[0075] As shown in Tables 2-3, the F-values of the standard samples used for low-temperature impact performance testing described in Examples 1-17 are all less than F. 0.05(9,10) =3.02, all t values are less than t 0.05(20+20-2) =2.024, all exhibiting good uniformity and stability. In Comparative Examples 1-4, the choice of talc powder differs from the scheme described in this invention, and the uniformity and stability fail to meet the requirements of the art. In Comparative Example 5, linear low-density polyethylene was not used, resulting in significantly worse uniformity and stability.
[0076] Comparing the uniformity and stability test results of Examples 1-3 and Examples 4-5, it can be found that the preferred composition of the standard sample for low-temperature impact performance testing described in this invention is: 60-80 parts of high-impact polystyrene, 15-25 parts of linear low-density polyethylene, 3-8 parts of compatibilizer, and 2-7 parts of talc.
[0077] Comparing the test results of Example 1 and Example 6, it can be found that modifying talc powder with titanate coupling agent can significantly improve the uniformity and stability of the standard sample.
[0078] Comparing the test results of Examples 1, 7 and 8, it can be found that the mass fraction of butadiene in the compatibilizer is preferably 60%-70%.
[0079] Comparing the test results of Example 1 and Example 9, it can be found that the lubricant is preferably a compound of liquid paraffin and zinc stearate.
[0080] Comparing the test results of Examples 1, 10-11 and 12-13, it can be found that when the mass ratio of talc powder with D50 particle size of 0.5-2μm to talc powder with D50 particle size of 5-8.5μm is 1:(1-2), the standard sample used for low-temperature impact performance testing has better uniformity and stability.
[0081] Comparing the test results of Example 1 and Example 17, it can be found that modifying talc can improve the overall performance of the standard sample.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A standard sample for low-temperature impact performance testing, characterized in that, The product comprises the following components in parts by weight: 50-90 parts high-impact polystyrene, 10-30 parts linear low-density polyethylene, 1-10 parts compatibilizer, 1-10 parts talc, and 0.3-5 parts additives; wherein the talc is a mixture of talc with a D50 particle size of 0.5-2 μm and talc with a D50 particle size of 5-8.5 μm; wherein the talc is modified with a coupling agent, and the mass fraction of the coupling agent is 1%-1% of the talc. 2.5%; the coupling agent is at least one of titanate coupling agent and silane coupling agent; the compatibilizer is styrene-butadiene-styrene block copolymer, wherein the mass fraction of butadiene in the styrene-butadiene-styrene block copolymer is 60%-70%; in the compound, the mass ratio of talc powder with a D50 particle size of 0.5-2μm to talc powder with a D50 particle size of 5-8.5μm is (1-1.5):(1-3).
2. The standard sample for low-temperature impact performance testing as described in claim 1, characterized in that, In the compound, the mass ratio of talc powder with a D50 particle size of 0.5-2 μm to talc powder with a D50 particle size of 5-8.5 μm is 1:(1-2).
3. The standard sample for low-temperature impact performance testing as described in claim 1 or 2, characterized in that, The modification method is as follows: at 100-110℃, the diluted coupling agent is added to talc powder and stirred evenly to obtain the talc powder modified by the coupling agent.
4. The standard sample for low-temperature impact performance testing as described in claim 1, characterized in that, The high-impact polystyrene comprises 60-80 parts by weight, the linear low-density polyethylene comprises 15-25 parts by weight, the compatibilizer comprises 3-8 parts by weight, and the talc comprises 2-7 parts by weight.
5. The standard sample for low-temperature impact performance testing as described in claim 1, characterized in that, The additives include 0.1-1 parts antioxidant, 0.1-2 parts light stabilizer, and 0.1-2 parts lubricant.
6. The standard sample for low-temperature impact performance testing as described in claim 5, characterized in that, The antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is at least one of internal lubricant and external lubricant, the internal lubricant is at least one of liquid paraffin, stearyl alcohol, polyester wax, microcrystalline wax and white oil, and the external lubricant is at least one of calcium stearate, zinc stearate, magnesium stearate and n-butyl stearate.
7. The standard sample for low-temperature impact performance testing as described in claim 6, characterized in that, The antioxidant is a compound of hindered phenolic antioxidant and phosphite antioxidant in a mass ratio of 1:(1-2), and the lubricant is a compound of internal lubricant and external lubricant in a mass ratio of 1:(1-2). The internal lubricant is liquid paraffin, and the external lubricant is zinc stearate.
8. A method for preparing a standard sample for low-temperature impact performance testing as described in any one of claims 1-7, characterized in that, Includes the following steps: (1) Mix the components evenly according to the proportions to obtain a premix; (2) The premixed material is added to a twin-screw extruder for melt extrusion, stranding, cooling, pelletizing and drying to obtain the standard sample used for low-temperature impact performance testing.
Citation Information
Patent Citations
Production process of notch shock sample
CN1074543C
Standard sample for notch impact strength detection and preparation method thereof
CN114773732A
Standard sample for unnotched impact performance detection and preparation method thereof
CN114674648A
